A systematic literature review and case study on the social impact of the other women’s contributions to education and dialogic feminism - Ruiz-Eugenio, Laura; Valls-Carol, Rosa; Flecha, Ainhoa; Aubert, Adriana (Frontiers in Sociology, 2024)
Feminism has been one of the most important social movements of the last centuries. Current societies have widely recognized their contributions. However, whereas ethnic diversity has been included in the movement, diversity in terms of academic background has not. Therefore, the contributions made by the “other women” from their daily lives, those with no university education (who belong to cultural minorities or not), remain on the margins of public debate. In the face of this reality, the plurality of all women has been building contributions to education and dialogic feminism. Based on Lidia Puigvert’s previous study on dialogic feminism and the “other women” movement, this article aimed to trace the social impact of “other women’s” contributions to education and dialogic feminism in their lives and communities. A qualitative case study has been developed that collects a systematic literature review, in-depth interviews with educators, focus groups, and communicative daily life stories with women who have participated in Schools as Learning Communities and democratic adult education associations in Spain over the last 20 years. The results provided evidence about the contributions of the “other women” in the development and expansion of successful educational actions that have generated social and educational transformations in themselves, their families, and their communities, such as Dialogic Gatherings and the prevention of gender violence, among others.